2012
DOI: 10.1016/j.urolonc.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of FISH and cytology in upper urinary tract surveillance after radical cystectomy for bladder cancer

Abstract: Objectives Cytology and fluorescence in situ hybridization (FISH) (Urovysion) assay are often used during upper urinary tract surveillance in patients following radical cystectomy with urinary diversion, without much available data regarding efficacy in this population. Here, we evaluate the value of FISH and cytology in detecting upper tract recurrence in the face of a urinary diversion. Materials and methods A review of our cystectomy database revealed 270 patients who had at least one FISH and/or cytology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 18 publications
(27 reference statements)
2
15
0
1
Order By: Relevance
“…Thus, an individualized approach to these patients should be considered with diagnostic evaluation commensurate with the degree of clinical suspicion. The role of adjunctive tests such as UroVysion (Abbott Molecular Inc) may further improve the diagnostic accuracy of UCy . The number of patients in the current series among whom these tests were performed was small and not sufficient for statistical analysis; therefore, it remains to be determined whether these ancillary techniques will help to identify recurrent UCa in patients with a diagnosis of AUC, as has been suggested in other studies…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, an individualized approach to these patients should be considered with diagnostic evaluation commensurate with the degree of clinical suspicion. The role of adjunctive tests such as UroVysion (Abbott Molecular Inc) may further improve the diagnostic accuracy of UCy . The number of patients in the current series among whom these tests were performed was small and not sufficient for statistical analysis; therefore, it remains to be determined whether these ancillary techniques will help to identify recurrent UCa in patients with a diagnosis of AUC, as has been suggested in other studies…”
Section: Discussionmentioning
confidence: 89%
“…Although the data for RRU are consistent with those reported in the literature, in which rates of urethral recurrence were reported to range from 6% to 10% 21,22 and upper urinary tract recurrence rates were lower (range, 1%-9%), [23][24][25][26] we found that UCy had higher sensitivity and specificity for RRU than those previously reported (sensitivity of 50%-80% and specificity of 85% to > 95%). 9,23,27 The slightly higher sensitivity for detecting RRU, without any loss in specificity, noted at the study institution may be explained by multiple factors, including the interest, experience, and expertise in urinary tract cytology of the cytopathologists practicing at this institution.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, by contrast to prior series [51], recent studies report on high sensitivity and specificity rates of 80–82% and 85–97%, respectively, of urinary cytology for the detection of recurrences in the remnant urothelium after RC while urine analyses by fluorescence in situ hybridization do not result in higher accuracy rates [52,53]. A recent report by Yafi et al [54] investigated patterns of recurrence among 1890 patients treated with RC for bladder cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The role ofFISH in the surveillance ofUTUC remains controversial, due to its poor performance in detecting low grade tumors, and high false positive rate (34)(35)(36)(37). Use ofFISH should be limited to cases in which there is a clinical suspicion of UTUC but urine cytology and other diagnostic modalities are negative or equivocal.…”
Section: Cytology Specimensmentioning
confidence: 99%